ASUHAN KEBIDANAN PADA NY. T USIA 28 TAHUN P1A2 POST CURETTAGE ATAS INDIKASI KEHAMILAN EKTOPIK TERGANGGU DENGAN TINDAKAN LAPAROTOMI DI RUMAH SAKIT SANTA ELIS - Lismawati .; Ria Oktaviance (STIKes Santa Elisabeth Medan, 2018)
Ectopic pregnancies are impaired including high-risk pregnancies that can be marked by either spotting or moderate bleeding that can be life-threatening to the mother. Based on worldwide WHO research, there is a maternal mortality of 500,000 lives per year and infant mortality in particular 10 million neonates per year. More than 60% of ectopic pregnancies occur in women aged 20-30 with low socio-economic and live in areas with high prevalence ofgonorrhea and tuberculosis prevalence. In Indonesia the maternal mortality rate is 330/100,000 live births. Maternal mortality is estimated at about 16,500-17,500 per year. One-third of them are due to falling-out services.Goals : Performing a Craving Care in Pregnant Women Mrs.T Age 28 years old G3P1A1 with Disturbed Ectopic Pregnancy using a seven step Varney approachMethods:Using descriptive method with case study approach implemented by author through approach of midwifery management. The case observed by the author in this Final Report is Mrs. T Age 28 years G3P1A1 with Disturbed Ectopic Pregnancy at Saint Elizabeth Hospital Medan Year 2018.Results: Gain real experience on the implementation of Midwifery care in pregnant women with Disturbed Ectopic Pregnancy at Saint Elizabeth Hospital Medan. Implementation of midwifery care in pregnant women with Disturbed Ectopic Pregnancy at Saint Elizabeth Hospital Medan is in accordance with the existing theory and hope can be used as input by students so as to provide broad insight into the quality of midwifery services according to midwifery care.Conclution : Standards through the approach of midwifery care management in pregnant women with Disturbed Ectopic Pregnancy.